The Disabled Male Gaze: Expressions of Desire and Emotion in Rory O'Shea Was Here - Gill, Michael (Disability Studies Quarterly, 2006)
This essay examines Rory O'Shea Was Here as a male melodrama. Chiefly utilizing theories of narrative prosthesis, problem bodies, and melodrama, a discussion of the disabled male gaze is forwarded. The result is a conclusion that within the film the objectification of Siobhan and the sentimentality of Michael and Rory's lives combine to further damaging gender politics and static representations of disabled characters. Despite the rhetoric of independence and self-sufficiency, Rory O'Shea Was Here employs a narrative of disability that offers an ultimate option of death instead of living with impairment. Rory O'Shea also endorses the view that the only meaningful relationships are authorized via professional routes.